2005
DOI: 10.1038/sj.cdd.4401793
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of osteoclast differentiation by the redox-dependent modulation of nuclear import of transcription factors

Abstract: This study sought to characterize the reduced glutathione (GSH)/oxidized GSSG ratio during osteoclast differentiation and determine whether changes in the intracellular redox status regulate its differentiation through a RANKL-dependent signaling pathway. A progressive decrease of the GSH/ GSSG ratio was observed during osteoclast differentiation, and the phenomenon was dependent on a decrease in total glutathione via downregulation of expression of the cglutamylcysteinyl synthetase modifier gene. Glutathione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 37 publications
3
60
0
2
Order By: Relevance
“…Recent evidences in a limited number of clinical studies have shown that ROS and/or antioxidant systems can be involved in the pathogenesis of bone loss (36)(37)(38)(39). In fact, oxidative stress activates the differentiation of preosteoclasts in osteoclasts and strengthens the bone resorption (18,40) (Figure 1). A significant increase in the number and activity of osteoclasts as well as in the tartrateresistant acid phosphatase level was observed when H2O2 was added to cultures of human marrow mononuclear cells (36).…”
Section: Oxidative Stress In Bone Remodelingmentioning
confidence: 99%
“…Recent evidences in a limited number of clinical studies have shown that ROS and/or antioxidant systems can be involved in the pathogenesis of bone loss (36)(37)(38)(39). In fact, oxidative stress activates the differentiation of preosteoclasts in osteoclasts and strengthens the bone resorption (18,40) (Figure 1). A significant increase in the number and activity of osteoclasts as well as in the tartrateresistant acid phosphatase level was observed when H2O2 was added to cultures of human marrow mononuclear cells (36).…”
Section: Oxidative Stress In Bone Remodelingmentioning
confidence: 99%
“…Redox status affects bone metabolism, including osteoclast differentiation (18). Thiol antioxidants are mediators of estrogen deficiency-induced bone loss.…”
mentioning
confidence: 99%
“…Oxidative stress, which results in changes in the redox status of cells, plays important roles in aging as well as in many diseases, including malignancies, diabetes, neurodegenerative diseases, atherosclerosis, ischemia, autoimmunity, and HIV infection (14,15) Free radicals also are involved in the pathogenesis of osteoporosis (6). Dietary antioxidants (18,25), levels of plasma antioxidants (5,24), and oxidative stress (4) have been all linked with bone density and the risk of hip fracture. At the cellular level, ROS have been found to stimulate osteoclastic bone resorption (22,23) and osteoclast differentiation (3,9), whereas free radical scavengers and antioxidants are inhibitory.…”
mentioning
confidence: 99%
“…Conversely, suppression of ROS during osteoclast differentiation inhibits ROS production, activation of MAP kinase, and osteoclast differentiation in BMMs (7,23). However, the total GSH content decreased during osteoclast differentiation; thus, GSH depletion by BSO, a specific inhibitor of GSH synthesis, inhibits osteoclastogenesis and bone pit formation in BMMs, suggesting the involvement of the GSH system in the process of osteoclastogenesis (9,10). In fact, we analyzed intracellular ROS in the condition of overexpression and depletion of Glrx2b in BMMs (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, GSH depletion by L-buthionine-(S,R)-sulfoximine (BSO), a specific inhibitor of GSH synthesis, inhibits osteoclastogenesis and bone pit formation by blocking nuclear importation of NF-κB and AP-1 in RANKL-mediated signaling in RAW 264.7 cells (10). Furthermore, antioxidant enzymes regulating ROS have been shown to http://bmbreports.org Fig.…”
Section: Introductionmentioning
confidence: 99%